Effects of Growth Regulators on Biomass and the Production of Secondary Metabolites in Peppermint (Mentha piperita) Micropropagated in Vitro - Santoro, Valeria Maricel (2013)
The effects of plant growth regulators on peppermint (Mentha piperita) cultured in vitro were studied for the purpose of maximizing growth and essential oil production in micropropagated plants. The basal medium was experimentally supplemented with the auxin 4-indol-3-ylbutyric acid (IBA) and the cytokinin 6-benzylaminopurine (BAP) individually and in combination. Supplementation with BAP alone resulted in the highest values for root length, root dry weight, shoot length, and numbers of nodes, leaves, and ramifications. Treatment with IBA alone or with IBA + BAP resulted in a ~50% increase in shoot fresh weight. The production of secondary metabolites was affected only by the addition of cytokinin, which resulted in a ~40% increase in the total yield of essential oils (EOs). Similar trends were observed for yields of the major EO components (menthone, menthol, pulegone, and menthofuran). Our findings demonstrate that the application of growth regulators increases EO production and biomass concomitantly in an herbaceous species rich in commercially valuable terpenes.